Cardiovascular magnetic resonance assessment of right ventricular function and pulmonary regurgitation in patients with repaired tetralogy of fallot: a single-center experience from Pakistan - Ullah, Zia; Wazir, Haseen Dil; Zia, Haris (International Journal of Pathology, 2025)
Background: Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disease requiring lifelong surveillance post-repair. Cardiovascular magnetic resonance (CMR) is the gold standard for assessing right ventricular function and pulmonary regurgitation, but limited data exists from South Asian populations. This study evaluates CMR findings in repaired TOF patients and assesses its role in pulmonary valve replacement (PVR) decision-making in a Pakistani cohort.Methods: This cross-sectional study included 80 consecutive patients with surgically repaired TOF who underwent CMR evaluation ≥2 years post-repair at Hayatabad Medical Complex, Peshawar (January 2020-December 2024). CMR was performed using 1.5 Tesla scanners with comprehensive protocols. Primary outcomes included right ventricular volumes, ejection fraction, and pulmonary regurgitation severity.Results: The cohort comprised 80 patients (mean age 14.5 ± 3.2 years, 56.25% male) with median 8.9 years since repair. Right ventricular dysfunction was prevalent with mean RVEF of 39 ± 11% and dilatation in 87.5% (mean RVEDVi - right ventricular end-diastolic volume index) 128.6 ± 32.4 mL/m²). Left ventricular function remained preserved (Left ventricular ejection fraction LVEF 53 ± 6%). Severe pulmonary regurgitation (>40%) occurred in 56.25% with mean regurgitation fraction of 36 ± 13%. Strong correlations existed between pulmonary regurgitation severity and right ventricular parameters (p < 0.001). PVR (Pulmonary valve replacement) was recommended in 81.3% of patients with 92.3% guideline adherence. Residual anatomical defects significantly worsened outcomes. Time since surgery correlated with progressive right ventricular deterioration (p < 0.001).Conclusions: High prevalence of right ventricular dysfunction and severe pulmonary regurgitation exists in Pakistani repaired TOF patients. CMR demonstrated strong correlations with clinical outcomes and proved essential for treatment planning. These findings emphasize CMR's critical role in guiding timely interventions and optimizing long-term management in resource-limited settings.